2021
DOI: 10.1016/j.eclinm.2020.100678
|View full text |Cite
|
Sign up to set email alerts
|

Congo red test for identification of preeclampsia: Results of a prospective diagnostic case-control study in Bangladesh and Mexico

Abstract: Background Misfolded proteins in the urine of women with preeclampsia bind to Congo Red dye (urine congophilia). We evaluated a beta prototype of a point-of-care test for the identification of urine congophilia in preeclamptic women. Methods Prospective diagnostic case-control study conducted in 409 pregnant women ( n = 204 preeclampsia; n = 205 uncomplicated pregnancies) presenting for delivery in two tertiary level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Five studies reported that CRDPT can be used to verify HDP. In a study by Bracken et al, 204 were pre-eclamptic and 205 normotensive women, the CRDPT was found to be effective in 155 and 50 respectively ( 30 ). In a study by Dobert et al which included 46 pre-eclamptic and 2,094 pregnant normotensives, the CRDPT was found to be effective in 2 and 4 respectively ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies reported that CRDPT can be used to verify HDP. In a study by Bracken et al, 204 were pre-eclamptic and 205 normotensive women, the CRDPT was found to be effective in 155 and 50 respectively ( 30 ). In a study by Dobert et al which included 46 pre-eclamptic and 2,094 pregnant normotensives, the CRDPT was found to be effective in 2 and 4 respectively ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Even though there are studies which found CRDPT to be effective in the detection of PE (21,22,(30)(31)(32), most of these studies had sampling bias (21,22,31,32), whereby higher sampling probability Evaluating sensitivity and specificity of CRDP test in detection of hypertensive disorder of pregnancy. 5, 6).…”
Section: Discussionmentioning
confidence: 99%
“…Their study also reported misfolded proteins in the urine of women with preeclampsia bound to Congo Red dye (urine congophilia or affinity for the amyloidophilic dye Congo Red) [37]. Ultimately, their study reported promising results from a prototype point-of-care test for the detection of urine congophilia [38]. A review by Navajas et al found nine publications from 2008 to 2020 that observed 132 proteins that were differently expressed in urine in PE cases compared to controls [22].…”
Section: Discussionmentioning
confidence: 95%
“…The latest results from a prospective diagnostic casecontrol study in Bangladesh and Mexico conducted by Bracken et al (40) were published in January 2021. The survey evaluated the success of a beta prototype test in identifying misfolded proteins in the urine of women suffering from PE.…”
Section: The Latest Studies On Singleton Pregnanciesmentioning
confidence: 99%